Identifikasi Struktur Bawah Permukaan Berdasarkan Pemodelan Kecepatan 1D Hasil Relokasi Hiposentrum Gempa di Pulau Lombok, Gunung Sinabung, dan Jailolo - Abraham Arimuko; Bayu M T F Nanda; Rasmid Rasmid (Himpunan Ahli Geofisika Indonesia (HAGI), 2020)
The determination of the subsurface structure can be done using a passive seismic method. This research makes use of earthquakes recorded on seismographs. The velocity profile from the relocation of the earthquake hypocenter shows the subsurface layers. The relocation method used is Joint Hypocenter Determination (JHD). As initial velocity parameters using global velocity models (IASPE91 & AK135) and local speed models in the Indonesian region from Koulakov and Madlazim. This study aims to determine the subsurface layer in an area that is experiencing tectonic earthquakes, volcanic earthquakes, and earthquake swarms. The relocated earthquake had a magnitude of MLv 3.0 to Mw 7.0 for the tectonic earthquake in Nusa Tenggara. Mount Sinabung magma moving in the main crater pipe caused a volcanic earthquake with a magnitude of MLv <5.5. Meanwhile, we used earthquake swarm data for the September 2017 period for the Jailolo region, North Maluku. From the results obtained, there is a high-velocity zone in the Lombok region at a depth of 50 km as the support of the Sunda Back Arc, while in Sinabung and Jailolo there is a low-velocity zone which is estimated to be liquid magma.